COPYRIGHT OF SCIENTIFIC WORKS BASED ON GENERATIVE AI: REGULATORY CHALLENGES OF ACADEMIC ETHICS - Gian Prima Natawijaya (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The use of Generative Artificial Intelligence (AI) in scientific writing creates new legal requirements, particularly regarding copyright protection, measures of originality, authorship, and academic integrity. Law No. 28 of 2014 concerning Copyright does not specifically regulate AI-based works, creating a normative gap when faced with the increasingly frequent use of AI-generated content in academic activities.This situation demands an update to the legal regulatory framework to address the dynamic development of AI technology in higher education. A hybrid regulatory approach, combining hard law and soft law, is the ideal framework for addressing these challenges. Hard law is needed as a basis for law enforcement and to ensure copyright protection for scientific works, while soft law plays a crucial role in shaping the behavior of academics through codes of ethics, institutional policies, and internal oversight and disciplinary mechanisms. The collaboration between these two instruments allows for a balance between legal certainty and academic ethical flexibility in regulating the use of AI. International legal practice demonstrates a global trend toward AI governance based on soft governance and self-regulation, without abandoning formal legal sanctions. While policies vary among the United States, the United Kingdom, and Japan, all countries agree in the principle that AI cannot replace humans as responsible creators (human authorship is mandatory). This concept provides an important foundation for Indonesia in formulating national policies that are not merely reactive, but anticipatory and in line with global regulatory developments. This research employs a normative legal research approach in the legal field, constructed on the basis of a study of legal principles, norms, dogmas, or rules, which are then analyzed comprehensively. However, the approach used in this research is normative-progressive, meaning it does not only examine legal dogma statically but also reinterprets existing positive legal norms critically and adaptively to the development of Generative AI technology, which has not yet been fully accommodated in the current Indonesian legal system.